PENINGKATAN HASIL BELAJAR PENJUMLAHAN MELALUI MODEL PROBLEM BASED LEARNING BERMEDIAKAN KARTU PASANGAN DI KELAS II SEKOLAH DASAR - Putri, Eka Jayanti; Benedictus Sudiyana; Binar Kustanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve the mathematics learning outcomes of second-grade students at SD Negeri Pranan 01 through the implementation of the Problem Based Learning (PBL) model with paired card media. The research employs a Classroom Action Research (CAR) design conducted in two cycles, with each cycle including planning, implementation, observation, and reflection. In the pre-cycle phase, only 30,77% of students achieved mastery in learning outcomes. The application of the PBL model in Cycle 1 resulted in an improvement to 69,23% of students reaching mastery, while Cycle 2 showed further improvement with 92,31% of students achieving mastery. Data were collected through observation sheets that recorded student engagement and participation, as well as learning outcome tests that assessed understanding of addition concepts before and after the implementation of the PBL model. Data analysis was conducted quantitatively to measure the improvement in learning outcomes and qualitatively to evaluate student activities during learning. The findings indicate that the PBL model with paired card media not only enhanced students' understanding of addition concepts but also improved student engagement and interaction during the learning process. This study suggests improvements in instructional delivery and the use of more varied learning media to achieve optimal learning outcomes and support the development of more innovative teaching practices in the future.